The Pedagogy Of The Prophets: A Systematic Literature Review Of Symbolic Actions, Vivid Imagery, And Public Oratory In Isaiah, Jeremiah, And Hosea - Edgar Tauran (Institute of Advanced Knowledge and Science, 2026)
This article synthesizes scholarship on the pedagogy of the Hebrew prophets, asking how Isaiah, Jeremiah, and Hosea used symbolic actions, vivid imagery, and public oratory as instruments of teaching. Prophetic literature has long been read through historical, theological, literary, and rhetorical lenses, yet its pedagogical character has rarely been treated as a single, integrated problem. Working from a PRISMA 2020-informed systematic literature review and a qualitative thematic synthesis, the study draws together research on prophetic sign-acts, metaphor, public address, embodied knowledge, covenant rhetoric, and religious formation. What emerges is a portrait of prophetic pedagogy as embodied, imaginative, public, affective, and transformative. Isaiah formed perception around holiness, justice, judgment, and hope through visual signs and poetic imagery. Jeremiah used enacted signs and temple oratory to puncture false security and press the community toward covenant accountability. Hosea turned family symbolism, marriage metaphor, and the language of healing into a dramatization of covenant infidelity and divine restoration. From these patterns the article proposes an integrated model in which divine message, prophetic medium, audience engagement, and covenantal learning outcome are inseparable. By reframing prophetic ministry as transformative pedagogy, the study speaks to biblical studies, theology, and faith-based education alike, offering a resource for contemporary religious educators and the institutions they serve.